Efektivitas Peran Auditor Internal dalam Memitigasi Risiko Kecurangan: Studi Literatur - Permana, Afrizal Adi; Nizar, Raihan; Kardina, Juliana Ayu; Afiyanti, Risqia; Repiyanti, Aprilia; Sipayung, Baren (CV. Kurnia Grup, 2025)
Fraud is a serious threat that can harm companies and undermine stakeholder trust. This study aims to examine the crucial role of internal auditors in fraud prevention and detection efforts, as well as analyze the factors influencing their effectiveness. Through a literature review of several studies published in accredited national and international accounting and auditing journals between 2018 and 2024, it was found that internal auditors play not only a supervisory role but also a strategic partner role in enhancing internal control systems and fostering an anti-fraud culture. The results of the study indicate that the competence and experience of auditors, their independence, top management support, and the use of information technology are key factors in optimizing the role of internal auditors in mitigating fraud risks. This study recommends that companies strengthen the internal audit function, enhance auditor competence, and utilize information technology in auditing to effectively prevent and detect fraud.